PERANCANGAN KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KOTABARU DENGAN PENERAPAN ARSITEKTUR MODERN - Suwandi, Muhammad Rafli; Anhar, Pakhri (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
The Population and Civil Registration Office of Kotabaru Regency is one of the Kotabaru Regency Regional Service agencies that functions in the affairs of structuring and issuing documents, population data through population registration, civil registration, processing population administration information and utilizing the results for public services. The occurrence of several factors such as the increase in total visits to the Office of the Population and Civil Registration is not matched by the capacity of the waiting room in the service room, the lack of air circulation and lighting so as to make the room conditions uncomfortable, as well as the ineffectiveness of circulation and workspace layout are the causes of problems with the level of service to the community. Therefore, the design stage applies the behavioral architecture approach method by identifying the behavior patterns of employees and the community in it and applying modern architectural concepts as an implementation of the results of the identification of occupant behavior so as to reach the functional point of the building. The data produces several physical variables that are adjusted to modern concepts such as space and layout, shape and facade size, color, texture, dimensions and proportions. The result of the design is to reach the functional point of the building so that the Office of the Population and Civil Registration service system to the community can be more optimal than before.